Actualization of Public Service Principles by the Ombudsman of the Republic of Indonesia - Habibullah, Abd Wachid; Rahayu, Karindra Yusnita Puji; Tsabita, Ananda Tsany; Aini, Diyanah Artu; Marantika, Dewi (Journal of Indonesian Constitutional Law, 2024)
The Ombudsman is an independent institution where in carrying out its duties and authorities the Ombudsman runs independently and there is no interference from other institutions or agencies. In this article, we use qualitative normative methods to present data critically and descriptively based on legal norms, legal theories, and legal doctrines regarding the Ombudsman. Using this method, we will present transparently the extent to which the ombudsman is effective in carrying out his functions and duties, especially in handling administration based on the principles of public service, of course, related to the General Principles of Good Government. With the results of the research we conduct, it can provide an overview of the existence of the Ombudsman whether it is optimal and significant for handling and improving the quality of public services with several challenges faced in it such as human resources and compliance from government agencies. With some of the things that we will describe, we will be able to underline the importance of the role and also the existence of the Ombudsman in serving in the community in accordance with the General Principles of Good Government.